Feasibility of repeat and bilateral submandibular gland needle biopsies in Parkinson's disease. (November 2019) - Adler, Charles H.; Serrano, Geidy E.; Zhang, Nan; Hinni, Michael L.; Lott, David G.; Mehta, Shyamal H.; Sue, Lucia I.; Intorcia, Anthony; Beach, Thomas G.
Abstract: Introduction: Submandibular gland (SMG) biopsies detect pathological alpha-synuclein (aSyn) in patients with Parkinson's disease (PD). The objectives of this study were to determine 1) the feasibility of performing a second SMG biopsy in previously biopsied patients, 2) the feasibility of doing bilateral SMG biopsies, 3) laterality of aSyn density, 4) whether aSyn density changes over time. Methods: Seven PD patients (6 males) previously having positive unilateral SMG biopsies underwent bilateral needle biopsies. Staining with a validated antibody to pathologic p-serine 129 aSyn was performed. Results: Mean age at time of second biopsy was 76 years and mean time between biopsies was 4.1 years. Five subjects had sufficient SMG tissue bilaterally and two only unilaterally for a total of 12/14 glands biopsied having sufficient tissue, all 7 subjects having sufficient tissue on at least one side, and all 12 glands being aSyn positive. There was a 4x increase in aSyn density on average in the repeat biopsy, with 5 subjects having an increase, one no change, and one a decrease in density. Side effects were similar to previous reports; mainly bruising, swelling, slight bleeding. Conclusions: This is the first published study of bilateral transcutaneous needle biopsies of the SMG in living patients with PD which showed better tissue acquisition and a change in aSyn density over time. While further study is needed, there is potential for SMG biopsies to serve as a tissue biomarker for PD disease progression and potentially as a peripheral outcome measure for anti-aSyn treatment. Highlights: Bilateral submandibular gland biopsies are feasible in patients with Parkinson's disease. There is alpha-synuclein density variability in submandibular glands. Alpha-synuclein density appears to increase over time. Submandibular gland biopsies could potentially serve as a disease progression marker. Submandibular gland biopsies could potentially assess anti-synuclein therapy effect.